Evaluating the causes and effects of construction disputes in private sector projects - Lim, Kelly Kah Yee (2024)
Construction projects have historically posed challenges within the private sector, leading to increased project costs, eroding stakeholder relationships, time overruns and so forth. This project delves into a comprehensive evaluation of the disputes, aiming to understand better what causes them and how they impact projects financially and operationally. A combination of quota and snowball sampling methods was utilized and 143 responses were collected. This research employs questionnaires to gather insights from clients, consultants and contractors in privately funded projects. After that, the collected data was subjected to reliability analysis, normality test and descriptive statistics. The causes of construction disputes were evaluated and ranked using frequency, severity and importance scores. The result shows that the top five important causes of construction disputes in private sector projects are lack of communication, payment delays, the owner’s arbitrary changes in the design, change of scope, and shortage in supply (Materials and Labour). Additionally, the Spearman Correlation Test revealed that the variables “Erosion of profit” and “Unfair Risk Allocation” had a most significant correlation of 0.418. Moreover, the delay in the progress of work and tension in communication have surfaced as foremost concerns, demonstrating the highest correlation count of 13. Furthermore, factor analysis successfully discovered 7 underlying factors from 25 causes of construction disputes in privately funded projects. The seven underlying principal factors are project vision misalignment, financial challenges, quality control concerns, contractual issues, site operational fragmentation, operational oversight challenges, and ethical and legal non-compliance. This research comprehensively analyzes construction disputes in privately funded projects, offering valuable insights into the causes and effects. By collecting data from a wide range of stakeholders and employing statistical analysis, it provides practical suggestions for enhancing construction projects. The findings have significant value for professionals in the industry, politicians and academics who want to improve project outcomes and reduce disputes in the private sector construction industry.